A theology of marriage: A biblical or a cultural construct? - van Eck, Ernest (Hervormde teologiese studies, 2020)
This article argues that the contemporary mainline understanding of marriage (theology of marriage), especially in the local South African denominational context, is not 'based on the Bible', but rather on a cultural construct. Moreover, this construct is not based on Judeo-Christian values and norms; it is the result of early Christianity's enculturation into the world of the Roman Empire. It is also argued that a definition of Christian marriage as being an institution originated by God, consisting of a monogamous and lifelong relationship between a man and a woman, cannot be based on the Bible. The reason for this is that the institution of marriage in ancient times was something totally different from what we understand today, the fact that the Bible also gives evidence of different understandings (forms) of marriage from the time of the patriarchs up to the 2nd century, and that Jesus, Paul and the Church Fathers preferred celibacy to marriage. Contribution This article aim to contribute to the current discussion, especially in the local South African denominational context, on the institution of marriage as being 'biblical', and its relationship to same sex-relations being typified as marriages.